BORNEAN KEELED PIT-VIPER - Veronica, Martin; Indraneil, Das (UNIMAS Publisher and Natural History Publications (Borneo) Sdn. Bhd., 2023)
The Bornean Keeled Pit-viper (Tropidolaemus subannulatus) is a strictly arboreal, venomous snake that is commonly encountered in Bako National Park. It possesses a heat-sensitive pit behind the nostrils, the source of its English common name. The species is widespread across many of the major islands of south-east Asia, including Borneo (Kalimantan, Indonesia; Labuan, Sarawak and Sabah, Malaysia and Brunei Darussalam), and the southern parts of the Philippines. Besides Bako, the species can be seen along the sandstone hills of Kubah National Park and Gunung Santubong National Park, Lambir Hills National Park, Ranchan Pool forests of Serian, Gunung Penrissen, the alluvial forests of Gunung Mulu National Park, the limestone hills of Bau, the peat swamps of Kota Samarahan, and many other localities across Borneo.